The Influence of Brand Image On Passenger Loyalty Through Acceptance Value Study On Low Cost Carrier Airline Passengers In Yogyakarta - Adipura Danang Maulana; Najmudin Najmudin; Sudarto Sudarto (International Journal of Business and Quality Research, 2024)
The airline industry is a highly competitive market, and understanding the factors that influence passenger loyalty is critical for airlines to maintain a sustainable competitive advantage. The aim of this research is to explore and understand the influence of brand image on passenger loyalty through value acceptance, with a focus on Low Cost Carrier airline passengers in Yogyakarta. This research aims to identify the extent to which the brand image of low-cost airlines influences passenger loyalty, as well as how the acceptance of value by passengers acts as a mediator in this relationship. This research will use a quantitative approach, by collecting data from a sample of low-cost airline passengers in Indonesia. Brand image is stated to have a significant influence on passanger loyalty, while the influence of brand image on perceived value and perceived value on passanger loyalty is stated to have no positive influence and is not significant, this is because LCC passengers are more focused on low prices than other factors.